Cost of mitigating climate change through reforestation in China - Zhang, Xianghua; Busch, Jonah; Huang, Yingli; Fleskens, Luuk; Qin, Huiyan; Qiao, Zhenhua (Frontiers in Forests and Global Change, 2023)
Reforestation is a potentially large-scale approach for removing CO2 from the atmosphere, thereby helping China achieve its goal of carbon neutrality by 2060. Although China has set ambitious national targets, the cost of mitigating climate change through reforestation has yet to be identified across space and time over the next 40 years. We construct spatially disaggregated marginal abatement cost curves for reforestation by modeling the effects of compensation for enhanced CO2 removals on reforestation. We project that carbon prices (compensation) of US20 tCO2−1 and US50 tCO2−1 would motivate land users in China to enhance reforestation by 3.35 Mha (2.65%) and 8.53 Mha (6.74%) respectively from 2020 to 2060 relative to the business-as-usual (BAU) scenario (127 Mha). Carbon dioxide removals through reforestation between 2020 and 2060 in China would be enhanced by 0.0124 GtCO2/yr (1.7%) at US20 tCO2−1 or 0.0315 GtCO2/yr (4.3%) at US50 tCO2−1, relative to the BAU scenario (0.740 GtCO2/yr). The cost potential of carbon dioxide removal demonstrates significant spatial heterogeneity. The top 10 provinces (Yunnan, Sichuan, Guangxi, Guizhou, Hunan, Guangdong, Heilongjiang, Jiangxi, Fujian, and Zhejiang), which comprise 73.19% of low-cost abatement potential, should be identified as priority areas for reforestation. Our results confirm the vast potential for low-cost CO2 removal through reforestation to address China’s carbon neutrality challenges while underscoring that targeting reforestation to regions with the greatest potential for low-cost CO2 removal would significantly reduce the cost burden.